A FUNGAL PATHOGEN OF LACE BUG AND LEAF EATING CATERPILLAR, TWO INSECT PESTS OF COCONUT PALM - Murali Gopal; Alka Gupta; B. Sathiamma; Chandrika Mohan; K.R. ChandraMohanan Nair; V.P. Soniya (International Coconut Community, 2000)
Lace bug, Stephanitis typica (D) and the leaf eating caterpillar, Opisina arenosella W. are two common pests in the coconut ecosystem. Lace bug is the vector of root (wilt) disease of coconut as it harbours and transmits the pathogenic “phytoplasma”. Leaf eating caterpillar is an outbreak defoliator pest. During field collection of these insects, it was observed that in some samples there was green colour sporolation on the cadavers of these insects. From such specimens a fungus was isolated and purified. It was identified as Aspergillus and then confirmed as A. flavus Link. In the laboratory, this fungus was tested for pathogenecity on hosts by different methods of spore application. It was observed that 80% S. typica nymphs died within 3 days and 80-90% of the O. arenosella larvae were mycosed within 3-4 days. In this paper, we discuss the above aspects in detail.